O9 The Effects of Coronavirus (COVID-19) on operative and work-based assessment (WBA) activity on surgical training. (8th April 2021) - ,; Clements, Joshua
Abstract: Background: COVID-19 has had a global impact on all aspects of healthcare including surgical teaching and training. The COVID-STAR qualitative study demonstrated a perceived negative impact of COVID-19 on numerous aspects of surgical training across all specialties and training grades. The aim of this study is to investigate how COVID-19 has affected operative case exposure and work-based assessments for surgeons in training. Methods: Anonymized data has been sought from the Intercollegiate Surgical Curriculum Programme (ISCP) database for operations and work-based assessments in each specialty, involving surgical trainees on an approved training programme at defined Pre-COVID (16/03/19 – 11/05/19) and COVID (16/03/2020 – 11/05/20) timepoints. Primary outcome measures are the percentage (%) difference in WBA and operative activity between time points respectively. Differences in training activity between time periods will be tested using Pearson χ2 and Kruskal–Wallis tests for categorical and continuous variables respectively. Results: This study has been approved by the ISCP Data Analysis, Audit and Research Group, and data will be managed in accordance with ISCP data governance. The hypothesis of this study is that COVID-19 has caused a reduction in the operative and WBA activity of trainees across all specialties. Conclusion: This study seeks to quantify the impact of COVID-19 on operative training activity and completion of WBAs in clinical practice. This information will inform major stakeholders involved in optimising surgical training in the COVID-19 recovery phase.